Postcards from Pluto : a tour of the solar system - Leedy, Loreen (New York : Holiday House, 1995)
Dr. Quasar gives a group of children a tour of the solar system, describing each of the planets from Mercury to Pluto.
G2
Keywords: Planets -- Juvenile literature; Planets; Solar system -- Juvenile literature; Solar system